The ecology of nasal colonization of Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus: the role of competition and interactions with host's immune response - Margolis, Elisa (BioMed Central, 2010)
BACKGROUND: The first step in invasive disease caused by the normally commensal bacteria Streptococcus pneumoniae, Staphylococcus aureus and Haemophilus influenzae is their colonization of the nasal passages. For any population to colonize a new habitat it is necessary for it to be able to compete with the existing organisms and evade predation. In the case of colonization of these species the competition is between strains of the same and different species of bacteria and the predation is mediated by the host's immune response. Here, we use a neonatal rat model to explore these elements of the ecology of nasal colonization by these occasionally invasive bacteria. RESULTS: When neonatal rats are colonized by any one of these species the density of bacteria in the nasal passage rapidly reaches a steady-state density that is species-specific but independent of inoculum size. When novel populations of H. influenzae and S. pneumoniae are introduced into the nasal passages of neonatal rats with established populations of the same species, residents and invaders coexisted. However, this was not the case for S. aureus - the established population inhibited invasion of new S. aureus populations. In mixed-species introductions, S. aureus or S. pneumoniae facilitated the invasion of another H. influenzae population; for other pairs the interaction was antagonistic and immune-mediated. For example, under some conditions H. influenzae promoted an immune response which limited the invasion of S. pneumoniae. CONCLUSIONS: Nasal colonization is a dynamic process with turnover of new strains and new species. These results suggest that multiple strains of either H. influenzae or S. pneumoniae can coexist; in contrast, S. aureus strains require a host to have no other S. aureus present to colonize. Levels of colonization (and hence the possible risk of invasive disease) by H. influenzae are increased in hosts pre-colonized with either S. aureus or S. pneumoniae.